Larger-volume capillary blood sampling is a valid alternative to assess progesterone and 17ß-estradiol for cycle phase identification in tactical female athletes - Schlie, Jennifer; Fellinger, Eva; Albrecht, Sina; Güldenstern, Jessica; Schmidt, Annette (Frontiers in Physiology, 2026)
IntroductionSerum-based hormone analysis is considered essential for determining menstrual cycle phases in sport and exercise science. However, its reliance on venous blood sampling limits applicability in field-based or operational contexts. This study evaluated the validity of larger-volume capillary samples obtained from the earlobe for the quantification of progesterone (P4) and 17ß-estradiol (E2) in comparison to venous blood sampling.Materials and methodTwelve eumenorrheic female soldiers (mean age: 24.4 ± 2.9 years; BMI: 24.4 ± 2.2 kg/m2) participated in a longitudinal protocol involving paired capillary and venous blood sampling twice weekly across one complete individual menstrual cycle. Blood was drawn from the earlobe (capillary, 100–250 µL) and antecubital vein (venous, 4 mL) and analyzed via ELISA for P4 and E2 concentrations.ResultsAll participants completed six or more sampling timepoints and had ovulatory cycles, with a mean cycle length of 28.3 ± 3.6 days and ovulation occurring on day 16.6 ± 4.7. On average, P4 concentrations were 1.6 ng/mL higher in venous compared to capillary samples, while E2 values were 0.34 pg/mL lower. The concordance correlation coefficients were 0.911 for P4 and 0.919 for E2, indicating good to very good agreement between the sampling methods. Repeated measures Bland-Altman analysis with mixed effects revealed minimal mean bias for both hormones, with acceptable limits of agreement. Repeated measures correlation coefficients were 0.915 and 0.982 for E2 and P4, respectively.Discussion and conclusionThe results demonstrate that earlobe-derived capillary sampling is a valid and practical alternative to venous sampling for hormonal assessment across the menstrual cycle. The method yielded robust results for both P4 and E2, with sufficient accuracy to support cycle phase classification and the detection of anovulatory or luteal-phase deficient cycles. The logistical advantages include minimal invasiveness, no need for medical personnel, and the ability to analyze the frozen samples at a later date. This makes capillary sampling particularly well suited for use with athletes and tactical populations. Future studies should explore its application in elite athletes and incorporate participant-reported burden to optimize feasibility in high-frequency sampling protocols.